Extreme luxury fashion: business model and internationalization process. Issue 3 (8th May 2017) - Guercini, Simone; Milanesi, Matilde
Abstract : Purpose: The purpose of this paper is to identify the defining characteristics of the extreme luxury fashion business model (ELFBM) and the relationship between this business model and the process of firm internationalization. The paper examines the potentially positive outcomes of differences and distances in the internationalization process of extreme luxury fashion companies. Design/methodology/approach: The paper presents and discusses the data collected during a five-year case analysis of an Italian luxury company. The main characteristics of the business model are identified in terms of products, manufacturing and sourcing, distribution channels, marketing communications and overall characteristics of consumers. The internationalization process is described, with a focus on the Russian market as an emblematic case, highlighting the role of distances – geographic, psychic and cultural – and liabilities, namely foreignness and outsidership in the international expansion of the firm. Findings: The findings of this paper highlight the main features and specific traits of the ELFBM characterized by a global and unique approach to the offer. This business model has in its origin the demand from certain foreign markets, and the elements of the country of origin of the firms coexist and are enhanced by the presence of specific characteristics of the destination countries in terms of niche consumers with economic and cultural characteristics and a strong perception of "Made in" and luxury goods. Originality/value: The paper contributes to previous studies on the relationships between business models and internationalization. It provides a framework for the "ELFBM, " in which internationalization is a constitutive element of a specific business model rather than a strategy for a business model already defined. Examining the positive side of differences and distances in the internationalization process of firms adopting such business model, the paper contributes to the international business theory and practice. It also expands research on luxury fashion defining an international company which is under-investigated, the extreme luxury fashion company, and the elements that constitute its business model.